Membrane Topology of Coronavirus E Protein - Maeda, Junko (Virology, 2001)
Coronavirus small envelope protein E has two known biological functions: it plays a pivotal role in virus envelope formation, and the murine coronavirus E protein induces apoptosis in E protein-expressing cultured cells. The E protein is an integral membrane protein. Its C-terminal region extends cytoplasmically in the infected cell and in the virion toward the interior. The N-terminal two-thirds of the E protein is hydrophobic and lies buried within the membrane, but its orientation in the lipid membrane is not known. Immunofluorescent analyses of cells expressing biologically active murine coronavirus E protein with a hydrophilic short epitope tag at the N-terminus showed that the epitope tag was exposed cytoplasmically. Immunoprecipitation analyses of the purified microsomal membrane vesicles that contain the same tagged E protein revealed the N-terminal epitope tag outside the microsomal membrane vesicles. These analyses demonstrated that the epitope tag at the N-terminus of the E protein was exposed cytoplasmically. Our data were consistent with an E protein topology model, in which the N-terminal two-thirds of the transmembrane domain spans the lipid bilayer twice, exposing the C-terminal region to the cytoplasm or virion interior.